THE USE OF AUTHENTIC MATERIALS IN SPEAKING CLASS AT THE SECOND SEMESTER STUDENTS OF ENGLISH EDUCATION STUDY PROGRAM OF TEACHER TRAINING AND EDUCATION FACULTY OF BANDAR LAMPUNG UNIVERSITY - Helta Anggia; Randi Setyadi (International Conference on Education and Language (ICEL), 2016)
This study was done in order to describe the students’ interest and motivation who were assigned by using the authentic materials through Schoology in speaking II class. The population of this study was the second semester students of English Education Study Program in UBL. Researcher used two kinds of instruments included the observation of students’ interest and motivation after they were assigned with authentic materials and the questionnaire aimed to describe their experiences during the treatment given. Result of this study showed that students’ interest and motivation improved and the treatment gave positive effect for their speaking ability.